Comparative study of DC/AC inverter control techniques for three phase grid connected PV system - Mahdi, Baqer Saleh; Al-fadheeli, Mohammad Ali; Sulaiman, Nasri; Hizam, Hashim; Shafie, Suhaidi; Abd Shehab, Mohanad (UIKTEN, 2022)
The goal of this project is to develop and analyze a three-phase grid-connected photovoltaic (PV) system with a 250KW power capacity with expandable property. The PI, Slide, and MPC methodologies are used to test three distinct inverter current control techniques. The dynamic performances of the three inverter control techniques are virtually comparable under grid connected working conditions, although the dynamic performances of the traditional PI control technique are slightly better and smoother than the other two inverter control techniques. The unity power factor criterion was reached by all techniques. The output power levels obtained using the sliding mode inverter control method are higher than those obtained using the PI and MPC methods. MPC's DC link voltage readings are also consistent and match the intended voltage levels.